ANALISIS KETENAGAKERJAAN PEKERJA DI BAWAH UMUR DALAM PERSPEKTIF HUKUM ISLAM DAN UNDANG-UNDANG NO. 13 TAHUN 2003 - Baharudin, Baharudin; Adnan, Idul (Universitas Teknologi Surabaya, 2024)
This research discusses the employment of underage workers from the perspectives of Islamic Law and Law No. 13 of 2003 on Employment. In Islam, the protection of children and underage workers is strictly regulated, emphasizing the importance of justice and safeguarding their basic rights. Law No. 13 of 2003 also sets forth various provisions aimed at protecting underage workers, though its implementation in the field often faces numerous challenges and deviations. This study aims to analyze how Islamic Law and Law No. 13 of 2003 regulate the employment of underage workers and assess the application of these regulations in practice. The research questions posed in this study are: 1) How does Islamic Law regulate the employment of underage workers? 2) How does Law No. 13 of 2003 on Employment provide protection for underage workers, and how is it implemented in practice? The research method used is a normative juridical approach with an analysis of legal texts and their implementation in the field. The findings show that although there are clear provisions in Islamic Law and national legislation, the implementation in the field still requires improvement to achieve optimal protection for underage workers.